Pemberdayaan Ekosistem Pesisir melalui Aksi Penanaman Mangrove untuk Pulau Pahawang - Muhammad Rizki Saleh; Mustarakh Gelfi; Maria Yosephine Simbolon; Nafisa Nandalianadhira; Nalendra Jagat Lumintang; Muhammad Mahendra Poetra Praja (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Pahawang Island is a smallest island designated for marine tourism, providing activities such as snorkeling, sunset and sunrise observation, and mangrove ecotourism in Pesawaran Regency, Lampung Province. The complexity of physical dynamics, paired with human activity, makes Pahawang vulnerable with several coastal issues such as erosion. One of a possible approach for preventing erosion on Pahawang Island is constructing natural coastal defenses by preserving the mangrove habitat along the shoreline. The community service aims to rehabilitate the mangrove ecosystem through mangrove planting activities. The method used in this community service is community empowerment through coordination and interviews with local village officials to assess the environmental conditions and identify planting locations, followed by the planting of mangrove seedlings from Rhizophora sp. species. Considering with ideal planting distance of 1 × 1 meter, approximately 100 mangrove seedlings were successfully planted within an area estimated to be 150 m². However, to ensure the long-term growth success of the planted mangroves, further monitoring and evaluation in the field are necessary.